Elevated presence of myeloid dendritic cells in nasal polyps of patients with chronic rhinosinusitis. Issue 2 (February 2015) - Poposki, J. A.; Peterson, S.; Welch, K.; Schleimer, R. P.; Hulse, K. E.; Peters, A. T.; Norton, J.; Suh, L. A.; Carter, R.; Harris, K. E.; Grammer, L. C.; Tan, B. K.; et al.
Summary Background Although chronic rhinosinusitis with nasal polyps (CRSwNP) is characterized by Th2 inflammation, the mechanism underlying the onset and amplification of this inflammation has not been fully elucidated. Dendritic cells (DCs) are major antigen‐presenting cells, central inducers of adaptive immunity and critical regulators of many inflammatory diseases. However, the presence of DCs in CRS, especially in nasal polyps (NPs), has not been extensively studied. Objective The objective of this study was to characterize DC subsets in CRS. Methods We used real‐time PCR to assess the expression of mRNA for markers of myeloid DCs (mDCs; CD1c), plasmacytoid DCs (pDCs; CD303) and Langerhans cells (LCs; CD1a, CD207) in uncinate tissue (UT) from controls and patients with CRS as well as in NP. We assayed the presence of DCs by immunohistochemistry and flow cytometry. Results Compared to UT from control subjects (n = 15) and patients with CRS without NP (CRSsNP) (n = 16) and CRSwNP (n = 17), mRNAs for CD1a and CD1c were significantly elevated in NPs (n = 29). In contrast, CD207 mRNA was not elevated in NPs. Immunohistochemistry showed that CD1c+ cells but not CD303+ cells were significantly elevated in NPs compared to control subjects or patients with CRSsNP. Flow cytometric analysis showed that CD1a+ cells in NPs might be a subset of mDC1s and that CD45+CD19−CD1c+CD11c+CD141−CD303−HLA‐DR+ mDC1s and CD45+CD19−CD11c+CD1c−CD141high HLA‐DR+ mDC2s were significantly elevated in NPs compared to UT from controls and CRSsNP, but CD45+CD11c−CD303+HLA‐DR+ pDCs were only elevated in NPs compared to control UT. Conclusion and Clinical Relevance Myeloid DCs are elevated in CRSwNP, especially in NPs. Myeloid DCs thus may indirectly contribute to the inflammation observed in CRSwNP.